Normotensive glaucoma - Lestak, Jan; Jiraskova, Nada; Zakova, Marketa; Stredova, Marketa (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2018)
This article provides an updated overview of the structural and functional changes in normotensive glaucoma and its variations from hypertensive glaucoma. The authors point out the less familiar facts in which both diagnostic groups differ.